The effects of instrument-assisted soft tissue mobilization rehabilitation exercise on range of motion, isokinetic strength, and balance in chronic ankle instability taekwondo players - Park, J. H.; Rhyu, H.-S.; Rhi, S.-Y. (Journal of Exercise Rehabilitation, 2020)
We aimed to investigate change the instrument-assisted soft tissue mobilization (IASTM) rehabilitation exercise on range of motion (ROM), isokinetic ankle strength, and balance. We included 20 elite taekwondo players (chronic ankle instability) in Korea. They were divided into the IASTM group (n=10), control group (n=10). IASTM group were exercised with IASTM rehabilitation exercise four times per week for 8 weeks. The remaining control group did not receive exercise intervention between tests and served as the control. A goniometer was used to measure dorsi-flexion (D/F), plantar-flexion (P/F), a dynamometer was used to measure ankle isokinetic strength, and plantar foot pressure was used to measure static balance. The data were analyzed using repeated-measures analysis of variance. Significant differences were observed between the two groups in IASTM group and control group: ROM (right P/F, P<0.001; right D/F, P<0.01; left P/F, P<0.000; left D/F, P<0.000), isokinetic strength (right P/F 60°, P<0.000; right D/F 60°, P<0.000; left P/F 60°, P<0.000; left D/F 60°, P<0.000; right P/F 180°, P<0.000; right D/F 180°, P<0.000; left: P/F 180°, P<0.000, left D/F 180°, P<0.000), and balance test (static eye open, P<0.000; static eye close, P<0.000; postural stability, P<0.041). These results suggest that IASTM rehabilitation exercise improves ankle stability, muscle power, and body balance in chronic ankle instability taekwondo players.